SYNTHESIS, STRUCTURAL STUDY AND ANTIBACTERIAL ACTIVITY OF Pd(II), Ru(III), Rh(III),Au(III) AND Pt(IV) COMPLEXES OF 4-NITRO-3-[4-(4-HYDROXYPHENYL)-2-METHYL-5-OXO-4,5-DIHYDRO-1H-IMIDAZOL-1-YL]IMINO-1,3-DIHYDRO-2H-INDOL-2-ONE - Al-Hasani, Rehab A M; Al-Abodi, A K; Kadem, S A (Al-Nahrain Journal of Science, 2018)
In this work lactone (1) was prepared from the reaction of amino acid with acetic anhydride which upon treatment with hydrazine afforded the lactame (2). The reaction of (2) with 5- nitroisatine obtained a new Schiff ’s base (L) in good yield. Complexes of Pd(II), Ru(III), Rh(III), Au(III) and Pt(IV) with the new Schiff ’s base (L) have been prepared .The compounds[1,2] were characterized by FT-IR , UV Spectroscopy, as well as the ligand (L) characterized by the same technique with elemental analysis (C.H.N). The prepared complexes were identified and their structural geometries were suggested by using elemental analysis (C.H.N), FI-IR and UV-Vis Spectroscopy, in addition to magnetic susceptibility and conductivity measurements. Metal to ligand [M:L] ratio was obtained for all complexes in (ethanol) using molar ratio method, which gave comparable results with those obtained for the solid complexes. As well as the apparent stability constant of the complexes have been studied with the time and their color were stable for more than (4) hours, Further more the molar absorptivites have been calculated. The antibacterial activity for the ligand (L) and their metal complexes were studied against three selected micro-organisms (Klesbsiella Pneumoniae, Staphylococcus aurous and Shigella flexneri), as well as the minimal inhibitory concentration (MIC) have been studied to determined the low concentration for inhibitor.